Yield of bean cultivars in two sowing dates in Frederico Westphalen-RS (Revista Brasileira de Iniciação Científica, 2020)
Bean culture is one of the main sources of vegetable protein, being sensitive to biotic and abiotic factors. The objective of this work was to evaluate plant population, grain productivity and thousand grain mass of five cultivars (BRS Campeiro, BRS Esplendor, IPR Uirapuru, IPR Tuiuiú and BRS Esteio), in two sowing dates (09/29/2018 and 10/24/2018). The experiment was conducted in Frederico Westphalen, RS, Brazil, in a bifactorial scheme using a randomized block design with four replications. The first sowing season was superior to the second, the best cultivar was BRS Campeiro and the worst was BRS Esplendor
Keywords: Phaseolus vulgaris L.; Productive Components.; Agroclimatic Zoning.